Data Supporting GoodVibes: automated thermochemistry for heterogeneous computational chemistry data - Luchini, Guilian; Alegre-Requena, Juan V.; Paton, Robert S. (Zenodo, 2020)
These files are provided in support of the use case in a recent manuscript showing the use of the Python package GoodVibes. This data set contains Gaussian optimization and frequency calculations on 25 molecules, along with 25 corresponding ORCA single point energy calculations, a YAML file to dictate and format the reaction pathway, and example outputs of the tabulated thermochemistry and a PNG of the potential energy surface graph output. To generate these output files, the command: python -m goodvibes *.log --spc DLPNO --pes PhPy.yaml --graph PhPy.yaml -t 353.15 --imag --invertifreq -5 --media ethanol -c 1 was run in the directory containing the calculation output (.log and .out) files.